The Campus Canopy, 1942-04-10 - The Campus Canopy, The Georgia State Woman's College (The Georgia State Woman's College, 1942)
The Campus Canopy, April 10, 1942. Vol. 31, No. 2. -- Guests To Attend Annual May Day-Play Day May 2 -- G.S.W.C. Has War Bond Campaign -- Co-Eds Will Begin Summer Quarter Mon., June Eighth -- Clubs Donate War Bonds As Campaign Progresses -- Ga. Glee Club Will Appear on April 15 -- To Reign May 2nd. -- GSWC’s Extra-Curricular Calendar Glows With Brilliant Activities From September Until June
Digitized from original print, Valdosta State University Archives and Special Collections, February 15, 2017.
Keywords: The Campus Canopy; The Georgia State Woman's College; VSC; VSU; Valdosta State College; Valdosta State University; GSWC; 1940s; 1942